Carrying Forward the Centennial Aspiration, Deeply Cultivating the Mobile Classroom: Construction, Practice, and Dissemination Implications of a School-Based Red Gene Study Tour Curriculum System ——A Case Study of the “Five-Power Education” Model of Harbin Xiaohong Middle School - Zhili Ren (Education Research on Study Tours and Practice, 2026)
Red study tours serve as an important educational vehicle that integrates small ideological and political classrooms with the broader social classroom. Harbin Xiaohong Middle School, a century-old school with profound revolutionary heritage, has developed a school-based, systematic, and curriculum-oriented red gene study tour curriculum system. This system is grounded in the school’s educational philosophy of “Virtue-Nurturing Xiaohong” and Xiao Hong spirit of “patriotism, self-improvement, benevolence, and innovation.” Adhering to the concept of “integrating red spirit into the soul and history into action,” the system is built upon a four-stage  developmental  sequence  of “cognition—experience—cultivation—promotion.” It establishes a “Five-Power” red education model, designs a three-tier progressive curriculum content of “foundation—embodiment—expansion,” and forms a closed-loop implementation process of “pre-tour guidance—on-site study—post-tour reflection.” Practice has shown that this system effectively stimulates students’ identification with red culture and their sense of patriotism, forming a replicable and scalable school-based study tour practice model. The “four-stage, three-tier” curriculum design logic and the “five-power collaboration” implementation paradigm proposed in this paper provide a systematic and operable practical pathway for the development of core competency-oriented red school-based study tour curricula. This serves as a significant reference for schools with distinctive cultural heritage in carrying out study tour education. Crucially, this achievement fully demonstrates the core leading role of the “Golden Seed” principal in the curriculum-based construction of study tours—where the principal acts as the “Golden Seed” of study tour leadership, transforming red resources into systematic curricula through curriculum-oriented thinking, and promoting the evolution of study tours from “activities” to “curricula” through systematic design, thereby offering a “replicable and transferable” paradigm for similar schools regionally and nationally.